Conceptual metaphors using plants as source domain in English and Vietnamese internet newspapers / Bùi Thị Phượng; NHDKH Dr Huỳnh Anh Tuấn - Bùi, Thị Phượng
The thesis is designed to investigate how conceptual metaphors using plants as source domain are used in English and Vietnamese internet newspapers in the light of cognitive perspective and discover the typical target domains from the source domain “plants” in two languages. The research is mainly carried out through the documentary analysis and descriptive study with the support and qualitative and quantitative approach. The author realizes that expressions using plants as source domain in English and Vietnamese internet newspapers are shown in 5 top target domains such as economy, emotion, human beings, social organization and idea. Besides, the writer re-builds a series of mappings from plant source domain upon target one, such as: the preparation for the growth of an object of target domain is the preparation for the growth of a plant, the initial stages of the growth is debut of the growth of a plant, the optimum stage of the growth is the flowering of a plant, etc. The results also show that there are many similarities and differences in conceptual metaphors of plant category in English and Vietnamese, for example: in source domain concepts and target domain, in conceptual structures of metaphors, in view, ways of thinking and culture. The study hopefully supplies some implications to help Vietnamese learners, teachers of English and translators better understand conceptual metaphor using plants as source domain in English and Vietnamese and then create the suitable tips to apply language flexibly